John Leeds Bozman family papers - Bozman, John Leeds, 1757-1823.; Kerr, John Bozman, 1809-1878.; Kerr, John Leeds, 1780-1844.; Richardson, Daniel, 1670-1722.; Richardson, Ruth, 1677-1728.
Correspondence, writings, notebooks, family papers, scrapbooks, and other papers primarily of John Leeds Bozman, John Bozman Kerr, John Leeds Kerr, and other members of the allied Bozman, Goldsborough, Kerr, Leeds, and Richardson families. Documents political, legal, and financial developments in the early history of Maryland, particularly the Eastern Shore. Includes John Leeds Bozman's poetry, political notebooks and a scrapbook of John Leeds Kerr, John Bozman Kerr's unpublished biography of Daniel Carroll, Daniel Carroll's will, and two volumes on Central America containing preliminary surveys for an isthmian canal, circa 1850. Also includes correspondence, business records, and estate papers of Daniel Richardson and his wife, Ruth Richardson, pertaining chiefly to trade with William Fishbourne, Ennion Williams, and other merchants of Philadelphia, Pa., and London, England; and manuscript copies of speeches delivered by Luther Martin and James McHenry in the Maryland legislature about the proceedings of the U.S. Constitutional Convention (1787). Correspondents include Edward Johnson Coale, Arnold Elzey, Charles Goldsborough, Nicholas Goldsborough, Robert Henry Goldsborough, Isaac Appleton Jewett, John Lloyd, Isaac Edward Morse, William Vans Murray, Benjamin Richardson, Charles S. Storrow, and William Tudor.
Historian and lawyer of Maryland.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carroll, Daniel, -- 1730-1796.; Carroll, Daniel, -- 1730-1796 -- Will; Coale, Edward Johnson, -- 1776-1832 -- Correspondence; Elzey, Arnold, -- active 1766 -- Correspondence; Fishbourne, William, -- 1677-1742.; Goldsborough, Charles, -- 1765-1834 -- Correspondence; Goldsborough, Nicholas, -- Correspondence; Goldsborough, Robert Henry, -- 1779-1836 -- Correspondence; Jewett, Isaac Appleton, -- 1808-1853 -- Correspondence; Lloyd, John, -- 1750 or 1751-1811 -- Correspondence; Martin, Luther, -- 1748-1826.; McHenry, James, -- 1753-1816.; Morse, Isaac Edward, -- 1809-1866 -- Correspondence; Murray, William Vans, -- 1760-1803 -- Correspondence; Richardson, Benjamin, -- active 1779 -- Correspondence; Storrow, Charles S. -- 1809-1904 -- Correspondence; Tudor, William, -- 1779-1830 -- Correspondence; Williams, Ennion; Bozman family; Goldsborough family; Kerr family; Leeds family; Richardson family; United States. -- Constitutional Convention -- (1787); Canals -- Central America; Canals, Interoceanic; Poetry; Central America; Eastern Shore (Md. and Va.) -- History; Great Britain -- Commerce -- Maryland; London (England) -- Commerce; Maryland -- Commerce; Maryland -- Commerce -- Great Britain; Maryland -- Commerce -- Pennsylvania; Maryland -- History; Maryland -- Politics and government; Pennsylvania -- Commerce -- Maryland; Philadelphia (Pa.) -- Commerce; United States -- Politics and government -- 1783-1789.; Historians; Lawyers